Sub-basin management and governance of rainwater and small reservoirs - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2011)
The project will identify socially acceptable land and water governance options and identify their livelihoods, health and environmental impacts, including spatial and temporal trade-offs at the watershed level.